MODEL PENILAIAN KINERJA DOSEN MENGGUNAKAN ESTIMASI BAYESIAN - Rini Yunita; Ramacos Fardela (LLDIKTI Wilayah X, 2019)
Lecturer’s performance is the actual behavior that displayed by each lecturer as the work achievement which produced based on the role. One way to measure the performance of lecturers through the assessment of student’s perception on the performance of lecturers in conducting lectures. By using Bayesian estimation, parameter test is used to estimate the lecturer's performance appraisal model to see how big the influence of each competence on lecturer's performance. Structural equality matrix: pedagogic competence, professional competence, personality competence, and social competence are represented in the equation . The results showed that the four competencies had a positive influence on lecturer performance, with the greatest influence given by pedagogic competence, followed by professional competence, personality competence, and social competence. Kinerja dosen merupakan perilaku nyata yang ditampilkan setiap dosen sebagai prestasi kerja yang dihasilkan sesuai dengan peranannya. Salah satu cara untuk mengukur kinerja dosen melalui penilaian persepsional mahasiswa terhadap kinerja dosen dalam melaksanakan perkuliahan. Dengan menggunakan estimasi Bayesian dilakukan pengujian parameter untuk mengestimasi model penilaian kinerja dosen untuk melihat seberapa besar pengaruh masing-masing kompetensi terhadap kinerja dosen. Matriks persamaan struktural: kompetensi pedagogik, kompetensi professional, kompetensi kepribadian, dan kompetensi sosial diwakili persamaan . Hasil penelitian menunjukkan bahwa keempat kompetensi memberikan pengaruh yang positif terhadap kinerja dosen, dengan pengaruh terbesar diberikan oleh kompetensi pedagogik, dilanjutkan dengan kompetensi professional, kompetensi kepribadian, dan kompetensi social.